Study of structural and photoluminescent properties of Ca8Eu2(PO4)(6)O-2 - Silva, C. C.; Filho, F. P.; Sombra, A. S. B.; Rosa, I. L. V.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer/plenum Publishers, 2008)
In this work it is presented for the first time the nanostructured hydroxyapatites doped with 0.5, 1.0 and 2.0 wt% of Eu3+ prepared at room temperature by the mechanical alloying technique. X-ray diffraction powder (XRD), infrared (IR) and Raman scattering spectroscopy, scanning electron microscopy (SEM), microhardness measurements as well as luminescent data of Eu3+ were used to investigate the structural and optical properties of these nanomaterials. The electrical and dielectrical analyses were used with the intention of having a better comprehension about the electromagnetic fields in pure and doped hydroxyapatites.
Keywords: hydroxyapatite; nanomaterial; europium; photoluminescence